2021
DOI: 10.1097/cce.0000000000000556
|View full text |Cite
|
Sign up to set email alerts
|

Patients With Coronavirus Disease 2019 Requiring Invasive Mechanical Ventilation in Mexico in the First, Second, and Exponential Growth Phase of the Third Wave of the Coronavirus Disease 2019 Pandemic

Abstract: A total of 3,197,108 coronavirus disease 2019 cases (2,537 cases per 100,000 people) and 252,080 deaths (200 deaths per 100,000 people) were recorded in Mexico as of August 20, 2021. There were 36,934 of 203,582 coronavirus disease 2019 patients (18.1%) that required invasive mechanical ventilation during the first wave of coronavirus disease 2019, 24,698 of 253,899 (9.7%) patients during the second wave, and 5,610 of 65,952 (8.5%) during the exponential growth phase of the third wave ( p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…This may represent a change in the indications for the use of these invasive techniques in Danish ICUs. Similar trends have been observed in other hospitals, regions and countries 3–6,11 …”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This may represent a change in the indications for the use of these invasive techniques in Danish ICUs. Similar trends have been observed in other hospitals, regions and countries 3–6,11 …”
Section: Discussionsupporting
confidence: 84%
“…There are reports on potential changes in characteristics, resource use and outcomes of ICU patients with COVID‐19 between the first wave and subsequent time periods, but most studies are from single centres or regions 3,4 . Furthermore, the interpretation of the few nationwide studies is limited by lack of data on patient characteristics and resource use 5,6 . In addition, the periodic heavy strain on many healthcare systems has likely influenced the selection, use of organ support and outcomes of ICU patients, 7–9 which may hamper the interpretation of any changes in these variables over time.…”
Section: Introductionmentioning
confidence: 99%
“…A number of smaller studies confirmed the invariably high mortality across the subsequent waves [ 2 , 25 ]. A number of studies found favorable time trends to lower mortality rate among COVID-19 patients admitted at the ICU, but the data were restricted to the first wave [ 1 , 3 5 , 26 , 27 ] or the differences in mortality between the waves were not adjusted for important patient characteristics [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] During the first and second waves of the coronavirus disease pandemic (COVID-19) in the United States, respectively, 18% and 10% of patients required invasive mechanical ventilation, and in the case of Mexico, this occurred in up to one-third of the patients, 4 a condition that has been associated with more than 82% mortality. 5,6 There was also an important role for the media in the generation of fear and the experience of community fear. 7,8 For these reasons, mental health manifestations could have been even more severe in family member of COVID-19 patients, also due to the highly invasive procedures applied, the visiting restrictions, and the high mortality that occurred at the beginning of the pandemic, which involved a profound impact on the quality of life of patients' families.…”
Section: Introductionmentioning
confidence: 99%